Acute Kidney Injury Associated with COVID-19 Infection: a Case Report - Duarte, T (2021)
SARS-Cov2 infection is a highly transmissible disease associated with serious pulmonary disease. Renal involvement is frequent and associated with poor prognosis; however, mechanisms of kidney injury are not well established. We present a SARS-Cov2 patient with severe acute kidney injury. Kidney biopsy findings revealed a pattern of acute tubular necrosis with isometric vacuolization of the proximal tubule. The interstitium and glomeruli were normal. Electronic microscopy showed multiple viral-like particles in both the glomeruli and proximal tubule. This case study shows how SARS-Cov 2 infection can result in different kinds of kidney lesion.